Teachers’ Strategies to Design Media to Implement Communicative Leaning in Public Schools - Mustafa, M. Nur; Hermandra, Hermandra; Zulhafizh, Zulhafizh (FKIP-Universitas Riau, 2019)
In order to implement communicative learning activities, ateacher must be able to design various means or media so that learningprocess keeps running well. A teacher is expected not to stutter indesigning media for various learning needs. The main purpose of thisstudy is to examine the strategies done by teachers in designing media toimplement communicative learning. This research is a descriptiveresearch in which the data were collected from teachers of MadrasahAliyah Negeri (public Islamic senior high schools) in Pekanbaru city. Theresearch sample was 36 teachers. The instrument used to collect the datawas a scale questionnaire. The data were descriptively analyzed. Eachitem of the questionnaire becomes the basis and the principal of theresearch analysis. The research findings reveal that to implementcommunicative learning, the teachers designed learning media. Thestrategies they used are making use of e-learning and making use ofvarious teaching and learning facilities, creating student worksheets andcompiling teaching materials, and presenting slides or other media inaccordance with the teaching materials. Each of the strategy is set at avery high standard. The teachers’ strategy to design media at the publicschools runs well. It can be seen from the average of the strategy that is4.48 and the average belongs to very high category. The data also clearlyreveal that the teachers are creative and innovative in designing media toimplement communicative learning.